SISTEM INFORMASI GEOGRAFIS EDUKASI DAN MITIGASI BENCANA BANJIR UNTUK SIAGA BENCANA DI KOTA PEKALONGAN - Ilyas, Agus; Setiawan, Tri Agus; Binabar, Sattriadi Wahyu (JURNAL LITBANG KOTA PEKALONGAN, 2020)
The city of Pekalongan is located on a low land, so there is a potential for floods every year. The efforts of the Pekalongan City government in overcoming floods are in the for m of making embankments, adding mangrove forests or through educating the community in protecting the environment. One of the existing problems is how to present data and information on flood area mapping and education to the community so that it can reduce existing victims. This research uses the Research and Development method, namely by collecting data on flood events, flood areas and flood impacts, evacuation facilities, public facilities and health and other support. From the results of the research carried out, it produces a geographic information system for web -based flood disaster mitigation and education where with this website it can be seen that flood and flood -prone areas, evacuation facilities, public facilities so that in the event of a flood d isaster can be given assistance quickly and precisely as needed, In addition, educational facilities are also produced to provide information and the impact of flooding. The purpose of this research is to help the Pekalongan city government in mitigating, educating and taking preventive action in dealing with flood disasters. Keywords: Flood area, website, mitigation, education, Pekalongan City